Ancient Mediterranean Incarceration - Larsen, Matthew D. C. (University of California Press, 2025)
A free ebook version of this title is available through Luminos, University of California Press's Open Access publishing program. Visit www.luminosoa.org to learn more. This book examines spaces, practices, and ideologies of incarceration in the ancient Mediterranean basin from 300 BCE to 600 CE. Analyzing a wide range of sources--including legal texts, archaeological findings, documentary evidence, and visual materials--Matthew D. C. Larsen and Mark Letteney argue that prisons were integral to the social, political, and economic fabric of ancient societies. Ancient Mediterranean Incarceration traces a long history of carceral practices, considering ways in which the institution of prison has been fundamentally intertwined with issues of class, ethnicity, gender, and imperialism. By foregrounding the voices and experiences of the imprisoned, Larsen and Letteney demonstrate the extraordinary durability of carceral structures across time and call for a new historical consciousness around contemporary practices of incarceration.